2022
DOI: 10.1016/j.vaccine.2021.12.041
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and missed or delayed vaccination in 26 middle- and high-income countries: An observational survey

Abstract: Background The COVID-19 pandemic has disrupted vaccination services and raised the risk of a global resurgence of preventable diseases. We assessed the extent of and reasons for missed or delayed vaccinations (hereafter ‘missed’) in middle- and high-income countries in the early months of the pandemic. Methods Participants were 28,429 adults from 26 middle- and high-income countries. From May to June 2020, participants completed an online survey on missed vaccination. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…The included studies used several approaches to study inequities in childhood vaccination inequities. Country-level income categories as defined by the World Bank ( accessed on 3 May 2022) to study variations in routine vaccination rates were reported for child populations in two studies for low-income countries (studies from Ethiopia [ 25 , 26 ]), three for lower-middle-income countries (studies from India [ 20 ] and Pakistan [ 14 , 16 ]), three for upper-middle-income countries (studies from Brazil [ 27 ], China [ 28 ] and Colombia [ 21 ]), four for high-income countries (three US studies [ 22 , 23 , 24 ] and UK [ 15 ]) and in a study comparing nine middle-income countries with 16 high-income countries [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The included studies used several approaches to study inequities in childhood vaccination inequities. Country-level income categories as defined by the World Bank ( accessed on 3 May 2022) to study variations in routine vaccination rates were reported for child populations in two studies for low-income countries (studies from Ethiopia [ 25 , 26 ]), three for lower-middle-income countries (studies from India [ 20 ] and Pakistan [ 14 , 16 ]), three for upper-middle-income countries (studies from Brazil [ 27 ], China [ 28 ] and Colombia [ 21 ]), four for high-income countries (three US studies [ 22 , 23 , 24 ] and UK [ 15 ]) and in a study comparing nine middle-income countries with 16 high-income countries [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Approaches for data collection varied across the studies. In four of them, the data collection was performed using a structured interview plus vaccination card records [ 16 , 20 , 25 , 27 ], four studies used a structured interview/survey only [ 15 , 26 , 28 , 29 ] and five studies used administrative records [ 14 , 21 , 22 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations